Adam Smith's Perspective on the Tension Between Education and Economy - Gallardo Eraso, Luis Alvaro (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper analyzes Smith's theory compared to the analyses present in the theories of economics of education and philosophy of education.  Adam Smith argues that education plays an essential role in the evolution and development of market societies. For Smith, education is not an aggregate of economic relations. Still, it intervenes to account for the pathologies that the market society develops in its evolution, related to ignorance, stupidity and the loss of sociability. This sense of pertinence is compared with that proposed by contemporary educational policies in higher education, from the analysis of the economics of education, which end up developing proposals that are functional to socio-economic logic. The perspective of education as a space for resolving pathologies is similar to the positions of the philosophy of education developed by Dewey and Mill, which, according to Kitcher (2009), seek to increase public knowledge for society. Smith's approach is adequate to understand the place of education in societies where mercantile logics predominate; however, his practical solutions are inadequate because they end up reproducing what he wants to avoid, the pathologies of the market. In this sense, the purpose is in tension with its applicability; this tension is nothing more than a sample of the problems that the market society develops when it tries to position education in the life space of society.